Type 2 diabetes mellitus and exercise impairment - Reusch, Jane E. B. (2013)
Limitations in physical fitness, a consistent finding in individuals with both type I and type 2 diabetes mellitus, correlate strongly with cardiovascular and all-cause mortality. These limitations may significantly contribute to the persistent excess cardiovascular mortality affecting this group. Exercise impairments in VO2 peak and VO2 kinetics manifest early on in diabetes, even with good glycemic control and in the absence of clinically apparent complications. Subclinical cardiac dysfunction is often present but does not fully explain the observed defect in exercise capacity in persons with diabetes. In part, the cardiac limitations are secondary to decreased perfusion with exercise challenge. This is a reversible defect. Similarly, in the skeletal muscle, impairments in nutritive blood flow correlate with slowed (or inefficient) exercise kinetics and decreased exercise capacity. Several correlations highlight the likelihood of endothelial-specific impairments as mediators of exercise dysfunction in diabetes, including insulin resistance, endothelial dysfunction, decreased myocardial perfusion, slowed tissue hemoglobin oxygen saturation, and impairment in mitochondrial function. Both exercise training and therapies targeted at improving insulin sensitivity and endothelial function improve physical fitness in subjects with type 2 diabetes. Optimization of exercise functions in people with diabetes has implications for diabetes prevention and reductions in mortality risk. Understanding the molecular details of endothelial dysfunction in diabetes may provide specific therapeutic targets for the remediation of this defect. Rat models to test this hypothesis are under study.